Pobreza entre os ocupados agrícolas no Brasil rural : uma análise de suas características e principais determinantes (2004-2012) - Couto, Ana Cristina Lima (2014)
The focus of this research is the theoretical and empirical approaches on the determinants of poverty, which refer on the one hand, to a set of socioeconomic factors (sex, color or race, age, age at which the individual started working, family composition, education, job position, residence location). On the other hand, there are the macroeconomic determinants of poverty (growth and income inequality), which are related to the so-called pro-poor growth. Proportionally, it is known that poverty is relatively higher in rural areas and among those who depend on farming activities. From this perspective, this study aims to study the characteristics of the busy farmers who live in the rural areas of Brazil, as well as to analyze the impacts of the main determinants of poverty for such a segment of the population. The National Household Survey database was used. A description of the profile of the busy farmers from 2004 to 2012 was carried out in order to evaluate the evolution of the indicators used, in addition to identify ways in which the situation of the poor people differs from the non-poor ones. In order to estimate the impact of socioeconomic factors on poverty, the logit regression model technique was used for the years 2004 and 2012. Finally, in order to investigate the impact of the macro determinants of poverty, the panel data model was applied in the units of the federation of Brazil from 2004 to 2012. Among the main results, it is highlighted the importance to be given to both, education and improvement by inserting the busy farmers into the labor market through policies that could reduce the problems related to the precarious ways of self-employed business and promote the most productive use of the workforce as well. Regarding the macroeconomic determinants of poverty, the elasticity analysis showed that the farm income has the greatest impact on poverty reduction, followed by a decrease in income inequality and increase of the education level.